Characterization of a yogurt-quality improving exopolysaccharide from Streptococcus thermophilus AR333. (August 2018) - Zhang, Hui; Ren, Wei; Guo, Qingbing; Xiong, Zhiqiang; Wang, Guangqiang; Xia, Yongjun; Lai, Phoency; Yin, Boxing; Ai, Lianzhong
Abstract: An exopolysaccharide EPS333 was produced by a ropy Streptococcus thermophilus strain AR333 when grown on reconstituted skim milk. The molecular weight, radius of gyration (Rg), hydrodynamic radius (Rh ) and intrinsic viscosity ([ η ]) of EPS333 were determined as 313.7 kDa, 33.96 nm, 25.98 nm, and 1.874 dL/g, respectively by high performance size exclusion chromatography (HPSEC). The conformational analysis demonstrated that EPS333 presented as compact and semi-stiff or stiff chain in aqueous solution. Monosaccharide analysis identified that EPS333 was composed of galactose, glucose and galactosamine in a molar ratio of 3: 2: 1. The backbone of EPS333 consisted of β-(1→3)-Gal p, β-(1→3, 6)-Glc p, α-(1→3)-2-Gal p NAc, and α-(1→4)-Glc p . The branch chain was terminated at O -6 position of β-(1→3, 6)-Glc p by α-T-Gal p . With the help of 1D & 2D NMR spectroscopy, the repeating unit of EPS333 was proposed. Further studies revealed that the in situ produced EPS333 could improve the quality of fermented milk to be close to the commercial product. Graphical abstract: Image 1 Highlights: EPS333 was proposed as a heteropolysaccharide with α-(1→3)-2-Gal p NAc in the backbone. EPS333 presented in compact and semi-stiff/stiff conformation in aqueous solution. In situ produced EPS333 could improve the quality of fermented milk significantly.